Breaking Invisible Barriers: Does Fast Internet Improve Access to Input Markets? - Banu Demir; Beata Javorcik; Piyush Panigrahi (CESifo GmbH, 2024)
This paper explores how improved internet infrastructure impacts supply chains and economic activity, focusing on Türkiye. Using the expansion of fiber-optic networks and firm-to-firm transaction data, we find that better connectivity shifts input sourcing to well-connected regions and diversifies supplier networks. We estimate a spatial equilibrium model with endogenous network formation and rational inattention and find that high-speed internet reduced information acquisition and communication costs. Enhanced connectivity increased real income by 2.2% in the median province. Our findings underscore the importance of digital infrastructure investments in fostering economic growth by improving supply chain efficiency and broadening firms' access to suppliers.
Keywords: L14; O33; R12; D83; H54; F14; D22; F15; L86; R58; O18; C63; Q55; E22; H41; 330; digitalization; production networks; supply chains